2007
DOI: 10.1016/j.aquatox.2007.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Combination of a pesticide exposure and a bacterial challenge: In vivo effects on immune response of Pacific oyster, Crassostrea gigas (Thunberg)

Abstract: To assess the impact of pollution induced by pesticides on Pacific oyster, Crassostrea gigas, health in France, in vivo effects of combined pesticide exposure and bacterial challenge on cell activities and gene expression in hemocytes were tested using flow cytometry and real-time PCR. As a first step, an in vivo model of experimental contamination was developed. Pacific oysters were exposed to a mixture of eight pesticides (atrazine, glyphosate, alachlor, metolachlor, fosetyl-alumimium, terbuthylazine, diuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 53 publications
(69 reference statements)
3
65
1
Order By: Relevance
“…A study with a mix of herbicides containing atrazine, diuron and isoproturon revealed effects on gene expression in the Pacific cupped oyster, Crassostrea gigas (Tanguy et al, 2005). Gagnaire et al (2007) studied also the impact of pesticides on C. gigas, monitoring gene expression in hemocytes by real-time PCR. The expression of genes involved in C. gigas hemocyte functions was up-regulated in pesticide-treated oysters compared to untreated oysters after a bacterial challenge.…”
Section: Other Effects Of Pesticides On Marine Bivalvesmentioning
confidence: 99%
See 1 more Smart Citation
“…A study with a mix of herbicides containing atrazine, diuron and isoproturon revealed effects on gene expression in the Pacific cupped oyster, Crassostrea gigas (Tanguy et al, 2005). Gagnaire et al (2007) studied also the impact of pesticides on C. gigas, monitoring gene expression in hemocytes by real-time PCR. The expression of genes involved in C. gigas hemocyte functions was up-regulated in pesticide-treated oysters compared to untreated oysters after a bacterial challenge.…”
Section: Other Effects Of Pesticides On Marine Bivalvesmentioning
confidence: 99%
“…It has been shown in several vertebrates and invertebrates that pesticides are capable of diminishing immune defenses and/or of modifying genomes. They may render animals more vulnerable to infectious diseases (Ross et al, 1996;Gagnaire et al, 2007). Although pesticide effects on marine bivalves have been already studied in bivalves, a few of reviews summarizing their different effects are available.…”
mentioning
confidence: 99%
“…The intensive irrigation and the use of pesticides provoked a deterioration of the water quality and quantity used to refill oyster ponds. This deterioration had strong impact on the oyster maturing (Gagnaire et al, 2007(Gagnaire et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that exposure to noylphenol at high enough levels has the ability to modulate Cg-galectin gene expression. In their study examining effects of pesticides on oyster immunity, Gagnaire et al (2007) suggested that pesticides modified the oyster immune response by inducing an up-regulation of genes involved in hemocyte functions and defense mechanisms as we see here. Despite this up-regulation, they saw higher mortality in bacterially treated oysters.…”
Section: Expression Of Lectinsmentioning
confidence: 78%
“…Subsequent to exposure, oysters mount two-fold defense mechanisms encompassed by cellular and humoral components that work in concert to recognize and eliminate pathogens. Despite lack of an acquired immunity that relies on immunological memory (i.e., antibodies), C. gigas has a developed system that can discriminate advantageous microorganisms from deleterious ones (Canesi et al, 2002;Gagnaire et al, 2007).…”
Section: Immune Systemmentioning
confidence: 99%